MOTIVATION AS A POSITIVE ATTITUDE FOR SUCCESSFUL LEARNING FOREIGN LANGUAGES - Daniyarova , Nargiza Farkhadovna (Innovative Development in Educational Activities, 2024)
It is generally acknowledged that two key factors that contribute to language learners’ success are their motivation and attitude. Reviewing and talking about motivation and attitude in language learning is the purpose of this article. Particularly, the research gives light on how scholars within the field perceive these two components, as well as how the two parts are combined in language learning. Language teachers should gain a deeper understanding of the two ideas from the discussions.